Pelatihan pembuatan kukis tepung pisang dengan fortifikan bubuk daun kelor kepada warga desa Nubamado Lembata Nusa Tenggara Timur - Nurholisah, Nurholisah; Nirmala, I Gusti Ayu Asti Devi; Althaf, Anindita Nareswari; Cahyani, Amalia Regita; Oktaviyani, Yanti; Crisdianto, Riki; Hidayat, Rosyid; Lena, Damasus Frederiko; Tukan, Gerardus Diri (STAI Auliaurrasyidin Tembilahan, 2025)
Nubamado Village, Lembata Regency has the potential for kepok bananas (Musa acuminata balbisiana Colla) which are still processed and utilized traditionally so this potential has little economic value. This training aims to provide knowledge and skills to residents to process this potential into functional food. The activity method is training. Activity results: partners are enthusiastic about participating in the training. Ingredients: 5 kg of fresh bananas, peeled, sliced, dried in the sun, then blended until smooth and filtered. Obtained 2.3 kg of flour. Young Moringa leaves are also dried and blended until they become a fine white powder. Add 200 grams of banana flour, one chicken egg, 50 grams of margarine, 10 grams of sugar and 5 grams of Moringa leaf powder. The dough is formed into semi-circular cookies with a diameter of 5cm and baked in the oven until dry. There were 62 cookies obtained. The training participants tasted the cookies produced and expressed their liking and joy because they had gained knowledge, skills and experience in making banana cookies.